Representasi Kepemimpinan Situasional dalam Menghadapi Krisis dari Film The Lion King - Sulistya, Vira Latifah; Amaliyah, Amaliyah; Dimysiqiyani, Erindah (CV. Pusdikra Mitra Jaya, 2025)
This study aims to understand how situational leadership is reflected in dealing with crises through the story in the movie The Lion King. This study is based on Hersey and Blanchard's situational leadership theory, which emphasizes four main styles, namely command, persuasion, participation, and delegation. The method used is qualitative descriptive analysis by examining the storyline, characters, and leadership dynamics of the main characters, especially Simba, in facing various challenges. The results show that situational leadership is clearly evident in Simba's journey, from his dependent childhood to his maturity as a king. However, each leadership style is present at different stages of development: the command style emerges when Simba still needs guidance, the persuasion style is evident when he receives encouragement to return, the participation style is seen when he works with his friends, and the delegation style emerges after he becomes king by placing trust in his environment. Overall, The Lion King not only depicts the dynamics of situational leadership in the face of crisis, but also presents valuable lessons about the importance of adaptive leadership that is relevant in real life.